Double-blind ureteral duplication- a rare cause of a neonatal abdominal cyst: A case report - Maria Vittoria Stern; Filomena Valentina Paradiso; Riccardo Rizzo; Sara Silvaroli; Francesco Pierconti; Lorenzo Nanni (EL-Med-Pub, 2024)
Background: Double-blind ureteral duplication (DBUD) is a rare condition in which one of the ureters in a duplicated system has no communication with the bladder or the renal pelvis. Case Presentation: We present a neonatal case of DBUD in a newborn girl, associated with a non-functional kidney, initially identified as an abdominal cystic anechoic mass during antenatal ultrasound. A stepwise diagnostic and management approach was undertaken, including prenatal and postnatal imaging, multidisciplinary consultation, and surgical intervention. Conclusion: Establishing a diagnosis of DBUD requires a systematic approach, incorporating comprehensive prenatal and postnatal assessments. This case is the first reported instance of DBUD diagnosed and treated in the neonatal period, highlighting the importance of early detection and intervention.